PERANAN LAZISMU DALAM MENGENTASKAN KEMISKINAN MASYARAKAT D.I YOGYAKARTA - Ahmad Danu Syaputra (Jurnal Media Ekonomi (JURMEK), 2016)
Zakat as one of the instruments of economic empowerment of the people is defined as giving to someone what is their right. And the demand itself is economic balance and not a buildup of wealth in a particular group. To be able to make this happen in the community, LAZISMU as the Amil Zakat Institution has an obligation to empower the community so that efforts to alleviate it in society are achieved. In this study the method used was qualitative by analyzing the data obtained from interviews with LAZISMU administrators. In addition to conducting interviews, data mining techniques are also carried out with documentation. Once collected, the data is processed and analyzed descriptively qualitatively. The results of this study indicate that poverty alleviation efforts carried out by LAZISMU in Yogyakarta can be said to have shown a big role because in conducting community empowerment it does not work alone but collaborates with Muhammadiya Institutions which in fact have been very experienced and have a wide range.